Process for Producing Partially Fluorinated Polymers - Patent application
Patent Information
- Application Number
- JP2023563950
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-04-19
- Filing Date
- 2022-04-11
- Publication Date
- 2025-03-19
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Fluoropolymers such as PVDF exhibit poor adhesion to metals, limiting their use in applications requiring strong interfacial bonding, particularly in electrodes for secondary batteries.
Subjecting vinylidene fluoride polymers to low-intensity ionizing radiation treatment, forming polar groups like hydroxyl groups, increases hydrophilicity and improves adhesion to metals, enhancing their suitability as binders in electrodes.
The treated polymers demonstrate significantly improved adhesion to metal surfaces, resulting in better performance as electrode binders, particularly in secondary batteries.
Abstract
Description
[Technical field]
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims priority to European Patent Application No. 21169087.0, filed April 19, 2021, the entire contents of which are incorporated by reference herein for all purposes.
[0002] The present invention relates to hydrophilic vinylidene fluoride polymers, processes for preparing these polymers, and their use to make articles characterized by improved performance. [Background technology]
[0003] Fluoropolymers such as vinylidene fluoride polymers (PVDF) are highly useful in a wide range of applications where good interfacial adhesion between the fluoropolymer and metal surfaces is highly desirable, such as automotive materials, pipes and fittings, bearings, linings, and containers, etc. However, fluoropolymers have very low surface energy and therefore poor adhesion to metals.
[0004] Surface treatments of fluoropolymers aimed at improving adhesion to metals are known and established in the art.
[0005] Fluoropolymers in the form of sheets, films and moldings have been chemically treated, subjected to electrical discharge using corona discharge and plasma, subjected to flame treatment, and subjected to physical treatments such as chemical adsorption procedures to improve their adhesion to metals.
[0006] Treatments applied to fluoropolymer particles to alter their chemical functionality and surface properties are also known in the art.
[0007] As an example, US Patent No. 6,300,641 discloses a process of irradiating a polymer surface of an article, such as a PVDF surface, with energized ionic particles in order to reduce the wetting angle of said surface and increase its adhesive strength. The irradiation is carried out in the presence of a reactive gas that chemically reacts with the polymer surface, thus resulting in a chemical modification of the surface of the article.
[0008] Among other surface treatments, JP 03-269024 A discloses a method for producing a surface-modified fluororesin which comprises irradiating the fluororesin with short-wavelength ultraviolet light. The method is preferably applied to fluororesin in the form of a film, but the method can also be applied to powders.
[0009] In the related art, PVDF has been used as an electrode binder in non-aqueous electrolyte secondary batteries. In general, PVDF homopolymers have poor adhesion to metals.
[0010] To face this problem, several solutions have been proposed. For example, WO 2008 / 129041 demonstrates that the inclusion of certain repeat units derived from (meth)acrylic monomers improves the adhesion of PVDF polymers to metals. However, depending on the active materials used, higher bonding properties between the active materials are still desired. Summary of the Invention
[0011] Applicants have recognized that a need remains for electrodes with improved adhesion to metals.
[0012] The Applicant has surprisingly found that when certain vinylidene fluoride (VDF) polymers are subjected to a low intensity irradiation treatment with ionizing radiation, said fluoropolymers are modified so as to obtain fluoropolymers which are characterized by a higher hydrophilicity and a significantly improved adhesion to metals, and which can therefore be suitably used as binders for electrodes used in secondary batteries.
[0013] Thus, in a first aspect, the present invention provides a method for producing a composition comprising the steps of: a) at least one electrode active material (AM); b) at least one binder (B), comprising at least one vinylidene fluoride (VDF) polymer [polymer (A)], the polymer (A) being obtained by a process comprising a step of irradiating polymer (F) with ionizing radiation at a dose of less than 70 kGy, the polymer (F) being (i) a repeating unit derived from vinylidene fluoride (VDF); (ii) optionally 0.01 mol % to 15.0 mol % of repeat units derived from a fluorinated comonomer (CF) other than VDF; at least one binder (B), wherein the aforementioned mole percentages refer to the total moles of repeat units of the polymer (F); c) at least one solvent (S); The present invention relates to an electrode-forming composition [composition (C)] comprising the above compound.
[0014] In another aspect, the present invention relates to the use of an electrode-forming composition (C) as defined above in a process for the manufacture of an electrode [electrode (E)], said process comprising the steps of: (A) providing a metal substrate having at least one surface; (B) providing an electrode-forming composition [composition (C)] as defined above; (C) applying the composition (C) provided in step (B) to at least one surface of the metal substrate provided in step (A), thereby providing an assembly comprising a metal substrate coated on at least one surface with said composition (C); (D) drying the assembly provided in step (C); (E) subjecting the dried assembly obtained in step (D) to a compression step to obtain the electrode (E) of the present invention; Includes.
[0015] In a further object, the present invention relates to an electrode [electrode (E)] that can be obtained by the process of the present invention.
[0016] In yet another object, the present invention relates to an electrochemical device comprising at least one electrode (E) of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] The term "repeating unit derived from vinylidene fluoride" (commonly also designated vinylidene difluoride, 1,1-difluoroethylene, VDF) is intended to mean a repeating unit of the formula CF2=CH2.
[0018] The polymer (A) is obtained by a process comprising the step of irradiating a polymer (F) with ionizing radiation at a dose of less than 70 kGy, the polymer (F) being (i) a repeating unit derived from vinylidene fluoride (VDF); (ii) optionally 0.01 mol % to 15.0 mol % of repeat units derived from a fluorinated comonomer (CF) other than VDF; Includes.
[0019] The above described irradiation process results in a polymer (A) that is significantly more hydrophilic than the starting polymer (F).
[0020] This irradiation process leads to the modification of the polymer (F) by the formation of polar groups, mainly hydroxyl groups, in the main chain of the VDF copolymer, which makes it hydrophilic with respect to water, resulting in a polymer (A) with a significantly reduced contact angle.
[0021] In one embodiment of the present invention, preferred polymers (A) have a contact angle of less than 73°, preferably less than 70°.
[0022] The term "contact angle" or "water contact angle" as used herein is defined as the angle formed between the tangent of a drop of water placed on a surface and the surface itself on which the drop resides.
[0023] A smaller contact angle means that the water droplet spreads more widely and thinly over the material surface, thereby increasing the surface's attractive properties to water, i.e., hydrophilicity.
[0024] To measure the contact angle of the polymer (A) in the form of a powder, a surface treatment is necessary. The film of the polymer (A) can be prepared by any known process starting from the polymer (A) in the form of a powder, for example by processing the composition of the polymer (A) in a suitable solvent by casting on an inert support, preferably a glass support, followed by suitable drying to remove the solvent. The contact angle measurement with water can then be carried out on the side of the film exposed to the substrate.
[0025] More specifically, the contact angle measurement for water is suitably carried out on polymer films cast from NMP solutions on glass surfaces at room temperature using a Contact Angle System OCA20 (DataPhysics Instruments GmbH) device. A drop of MilliQ water is automatically deposited on the film surface exposed to the glass substrate during film preparation. The contact angle is determined as the average of 10 measurements.
[0026] Excellent results have been obtained with polymers (F) which contain at least 85 mol % of repeat units derived from VDF.
[0027] Polymer (F) is preferably a semi-crystalline polymer.As used herein, the term "semi-crystalline" means that in DSC analysis, in addition to the glass transition temperature Tg, the fluoropolymer has at least one crystalline melting point.For the purposes of the present invention, semi-crystalline fluoropolymer is intended herein to denote a fluoropolymer that advantageously has a heat of fusion determined according to ASTM D 3418 of at least 0.4 J / g, preferably at least 0.5 J / g, more preferably at least 1 J / g.
[0028] Preferably, the intrinsic viscosity of the polymer (F), measured in dimethylformamide at 25° C., is comprised between 0.1 l / g and 0.80 l / g, more preferably between 0.15 l / g and 0.45 l / g, even more preferably between 0.25 l / g and 0.35 l / g.
[0029] The polymer (F) used in the process of the present invention usually has a melting temperature (T m ).
[0030] The melting temperature can be determined from a DSC curve obtained by differential scanning calorimetry (hereinafter also referred to as DSC). When a DSC curve shows multiple melting peaks (endothermic peaks), the melting temperature (T m ) is determined based on the peak with the largest peak area.
[0031] The polymer (F) may optionally contain repeat units derived from one or more fluorinated comonomers (CF) different from VDF.
[0032] The term "fluorinated comonomer (CF)" is intended herein to denote an ethylenically unsaturated comonomer that contains at least one fluorine atom.
[0033] Non-limiting examples of suitable fluorinated comonomers (CF) include, inter alia: (a) C2 to C8 fluoro and / or perfluoroolefins, such as tetrafluoroethylene (TFE), hexafluoropropylene (HFP), pentafluoropropylene and hexafluoroisobutylene; (b) C2-C8 hydrogenated monofluoroolefins, such as vinyl fluoride, 1,2-difluoroethylene and trifluoroethylene; (c)Formula CH2=CH-R f0 (In the formula, R f0 is a C1-C6 perfluoroalkyl group), (d) Chloro-, and / or bromo-, and / or iodo-C2-C6 fluoroolefins such as chlorotrifluoroethylene (CTFE). Includes:
[0034] In a preferred embodiment, the polymer (F) contains 0.1 to 10.0 mol %, preferably 0.3 to 5.0 mol %, more preferably 0.5 to 3.0 mol % of repeat units derived from the above-mentioned fluorinated comonomer (CF).
[0035] In another preferred embodiment, the polymer (F) does not comprise a fluorinated copolymer (CF).
[0036] The polymer (F) can be obtained by polymerizing the VDF monomer and optionally at least one comonomer (CF) in suspension in an organic medium or in aqueous emulsion, according to procedures known in the literature.
[0037] The procedure for preparing the polymer (F) comprises polymerization in an aqueous medium in the presence of the radical initiator vinylidene fluoride (VDF) and, optionally, at least one comonomer (CF), optionally in the presence of a chain transfer agent and a dispersing agent in the reaction vessel.
[0038] Generally, the process of the invention is carried out at a temperature of at least 20°C, preferably at least 30°C, more preferably at least 35°C.
[0039] When the polymerization is carried out in suspension, the polymer (F) is typically provided in the form of a powder.
[0040] When the polymerization to obtain the polymer (F) is carried out in emulsion, the polymer (F) typically comes in the form of an aqueous dispersion (D) and can be used as obtained directly by emulsion polymerization or after a concentration step. Preferably, the solids content of the polymer (F) in the dispersion (D) is in the range comprised between 20 and 50% by weight.
[0041] The polymer (F) obtained by emulsion polymerization can be isolated from the aqueous dispersion (D) by concentration and / or coagulation of the dispersion and can be obtained in powder form by subsequent drying.
[0042] The polymer (F) in the form of a powder can optionally be further extruded to obtain the polymer (F) in the form of pellets.
[0043] The extrusion is suitably carried out in an extruder. The duration of the extrusion suitably ranges from a few seconds to 3 minutes.
[0044] The polymer (F) can be dissolved in any suitable organic solvent to obtain a solution (sol) of the polymer (F). Preferably, the solid content of the polymer (F) in the solution (sol) is in the range of 2 to 30% by weight.
[0045] Non-limiting examples of organic solvents suitable for dissolving the polymer (F) are N-methyl-2-pyrrolidone (NMP), N,N-dimethylformamide, N,N-dimethylacetamide, dimethylsulfoxide, hexamethylphosphamide, dioxane, tetrahydrofuran, tetramethylurea, triethyl phosphate, and trimethyl phosphate, aliphatic ketones, cycloaliphatic ketones, cycloaliphatic esters. These organic solvents can be used alone or in a mixture of two or more species.
[0046] The polymer (F) to be subjected to the ionization treatment is preferably in the form of a powder.
[0047] The step of irradiating the polymer (F) can thus be carried out with any ionizing radiation, which may be α-rays, β-rays, γ-rays or electron beams, however, from the standpoint of safety and reactivity, β-rays, γ-rays and electron beams are preferred.
[0048] Irradiation must be carried out in the presence of oxygen. Irradiation can be carried out in air.
[0049] It is known in the art that irradiation treatment leads to a reduction in the molecular weight of irradiated polymers due to chain scission of the polymer chains, the formation of double bonds along the polymer chains, and the formation of oxygen-containing polar groups (Taguet, A., Ameduri, B., Boutevin, B. (2005). Crosslinking of Vinylidene Fluoride-Containing Fluoropolymers. In: Crosslinking in Materials Science. Advances in Polymer Science, vol 184. Springer, Berlin, Heidelberg). The polar groups are mainly generated by the decomposition of hydroperoxides formed by the reaction of oxygen with radicals in the backbone of the polymer chain. Subsequent decomposition of these can also lead to the formation of hydroxyl groups, which explains the increase in the hydrophilicity of the polymer.
[0050] Irradiation in the presence of oxygen may further promote the formation of such hydroxyl groups (Choi, Y. Kim, M. Preparation and characterization of polyvinylidene fluoride by irradiating electron beam. Appl. Chem. Eng. 22, 353-357).
[0051] The irradiation step of the process of the present invention is preferably carried out at a dose of from 0.1 kGy to 70 kGy, more preferably from 1 kGy to 40 kGy, and even more preferably from 1 kGy to 20 kGy.
[0052] The applicant has surprisingly found that under such mild conditions, polymer (F) can be modified to become hydrophilic, with minimal damage to the original backbone structure of polymer (F). This is mainly due to the low intensity radiation used. Thus, the monomer composition of polymer (A) and polymer (F) is substantially identical. At the same time, the low intensity radiation used in the process of the present invention allows polymer (A) to become hydrophilic due to the presence of polar groups in the backbone of the polymer chain.
[0053] In the present invention, a decrease in the contact angle refers to the formation of hydrophilic groups on the surface of the polymer, and the formation of hydrophilic groups will refer to a decrease in the contact angle.
[0054] The electrode-forming composition (C) of the present invention comprises one or more electroactive materials (AM). For the purposes of the present invention, the term "electroactive material" is intended to denote a compound capable of incorporating or inserting into its structure and subsequently releasing therefrom alkali or alkaline earth metal ions during the charging and discharging phases of an electrochemical device. The electroactive material is preferably capable of incorporating or inserting and releasing lithium ions.
[0055] The nature of the electroactive material in the electrode-forming composition of the present invention depends on whether said composition is used to prepare a positive electrode [electrode (Ep)] or a negative electrode [electrode (En)].
[0056] When forming a positive electrode for a lithium ion secondary battery, the electroactive compound may include a lithium-containing compound.
[0057] In a preferred embodiment, the lithium-containing compound may be a metal chalcogenide of the formula LiMQ2, where M is at least one metal selected from transition metals such as Co, Ni, Fe, Mn, Cr, and V, or metals such as Al, and mixtures thereof, and Q is a chalcogen such as O or S. Among these, it is preferable to use lithium-based composite metal oxides of the formula LiMO2 (wherein M is the same as defined above). Preferred examples thereof include LiCoO2, LiNiO2, LiNi x Co 1-x O2(0 <x<1)、LiNi a Co b Al c O2 (a+b+c=1) and spinel structured LiMn2O4.
[0058] In another embodiment, when forming a positive electrode for a lithium ion secondary battery, the electroactive compound is further represented by the formula M1M2(JO4): f E 1-f where M1 is lithium, which may be partially replaced by another alkali metal representing less than 20% of the M1 metal; M2 is a transition metal at an oxidation level of +2 selected from Fe, Mn, Ni or mixtures thereof, which may be partially replaced by one or more additional metals at an oxidation level of +1 to +5 and representing less than 35% of the M2 metal; JO4 is any oxyanion, where J is any of P, S, V, Si, Nb, Mo or combinations thereof; E is a fluoride, hydroxide or chloride anion; and f is the mole fraction of the JO4 oxyanion, typically comprised between 0.75 and 1.
[0059] M1M2(JO4) defined above f E 1-f The electroactive material is preferably phosphate-based and may have an ordered or modified olivine structure.
[0060] More preferably, the electroactive compound when forming the positive electrode has the formula Li 3-x M'y M'' 2-y (JO4)3, where 0≦x≦3 and 0≦y≦2, M′ and M″ are the same or different metals, at least one of which is a transition metal, and JO4 is preferably PO4, which may be partially substituted with another oxyanion, where J is any of S, V, Si, Nb, Mo or combinations thereof. Even more preferably, the electroactive compound has the formula Li(Fe x Mn 1-x LiFePO4 is a phosphate-based electroactive material, where 0≦x≦1, and x is preferably 1 (i.e., lithium iron phosphate of the formula LiFePO4).
[0061] In a most preferred embodiment, the electroactive material for the positive electrode is represented by the general formula (III): LiNi x M1 y M2 z Y2(III) (wherein M1 and M2 are the same or different and are transition metals selected from Co, Fe, Mn, Cr and V, 0.5≦x≦1, where y+z=1−x, and Y preferably represents a chalcogen selected from O and S).
[0062] The electroactive material in this embodiment is preferably a compound of formula (III) in which Y is O. In a further preferred embodiment, M1 is Mn and M2 is Co or M1 is Co and M2 is Al.
[0063] Examples of such active materials include LiNi x Mn y Co z O2 (hereinafter referred to as NMC), and LiNi x Co y Al z O2 (hereinafter referred to as NCA).
[0064] Specifically, LiNi x Mn y Coz The content ratio of manganese, nickel, and cobalt relative to O2 can be varied to tune the power and energy performance of the battery.
[0065] In a particularly preferred embodiment of the invention, the compound AM is a compound of formula (III) as defined above, where 0.5≦x≦1, 0.1≦y≦0.5, and 0≦z≦0.5.
[0066] Non-limiting examples of suitable electroactive materials for the positive electrode of formula (III) include, among others: LiNi 0.5 Mn 0.3 Co 0.2 O2, LiNi 0.6 Mn 0.2 Co 0.2 O2, LiNi 0.8 Mn 0.1 Co 0.1 O2, LiNi 0.8 Co 0.15 Al 0.05 O2, LiNi 0.8 Co 0.2 O2, LiNi 0.8 Co 0.15 Al 0.05 O2, LiNi 0.6 Mn 0.2 Co 0.2 O2, LiNi 0.8 Mn 0.1 Co 0.1 O2, LiNi 0.9 Mn 0.05 Co 0.05 O2 Includes:
[0067] Compound: LiNi 0.8 Co 0.15 Al 0.05 O2, LiNi 0.6 Mn 0.2 Co 0.2 O2, LiNi 0.8 Mn 0.1 Co 0.1 O2, LiNi 0.9 Mn 0.05 Co 0.05 O2 is particularly preferred.
[0068] When forming a negative electrode for a lithium ion secondary battery, the electroactive compound may preferably include one or more carbon-based materials and / or one or more silicon-based materials.
[0069] In some embodiments, the carbon-based material can be selected from graphite, such as natural or artificial graphite, graphene, carbon black, and carbon nanotubes (CNTs).
[0070] These materials may be used alone or as a mixture of two or more of them.
[0071] The carbon-based material is preferably graphite.
[0072] The silicon-based compound may be one or more selected from the group consisting of chlorosilane, alkoxysilane, aminosilane, fluoroalkylsilane, silicon, silicon chloride, silicon carbide, and silicon oxide. More specifically, the silicon-based compound may be silicon oxide or silicon carbide.
[0073] When present in the electroactive compound, the silicon-based compound is included in an amount ranging from 1 to 60% by weight, preferably from 5 to 20% by weight, based on the total weight of the electroactive compound.
[0074] The electrode-forming composition of the present invention comprises at least one solvent (S).
[0075] The solvent in the cathode-forming composition may include one or more organic solvents, preferably polar solvents, examples of which may include: N-methyl-2-pyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, dimethylsulfoxide, hexamethylphosphamide, dioxane, tetrahydrofuran, tetramethylurea, triethylphosphate, and trimethylphosphate. These organic solvents may be used alone or in mixtures of two or more species.
[0076] The electrode-forming composition of the present invention typically contains 0.5% to 10% by weight, preferably 0.7% to 5% by weight, of polymer (A). The composition also contains 80% to 99% by weight of an electroactive material. All percentages are weight percentages of the total "solids content." By "solids content" is intended "all of the raw materials of the electrode-forming composition of the present invention, excluding the solvent."
[0077] In general, in the electrode-forming composition of the present invention, the solvent is 10% by weight to 90% by weight of the total amount of the composition. In particular, in the case of an anode-forming composition, the solvent is preferably 25% by weight to 75% by weight, more preferably 30% by weight to 60% by weight of the total amount of the composition. In the case of a cathode-forming composition, the solvent is preferably 5% by weight to 60% by weight, more preferably 15% by weight to 40% by weight of the total amount of the composition.
[0078] The electrode-forming composition of the present invention may further comprise one or more optional conductive agents to improve the electrical conductivity of the resulting electrode made from the composition of the present invention. Conductive agents for batteries are known in the art.
[0079] Examples of these may include: carbon black, graphite fine powders, carbon nanotubes (CNT), graphene, or carbonaceous materials such as fibers, or fine powders or fibers of metals such as nickel or aluminum. The optional conductive agent is preferably carbon black. Carbon black is available, for example, under the brand names Super P® or Ketjenblack®.
[0080] When present, the conductive agent is different from the carbon-based material described above.
[0081] The amount of the optional conductive agent is preferably 0 to 30% by weight of the total solid content in the electrode-forming composition. In particular, in the case of a cathode-forming composition, the amount of the optional conductive agent is typically 0 to 10% by weight, more preferably 0 to 5% by weight, of the total solid content in the composition.
[0082] For anode-forming compositions that do not include a silicon based electroactive compound, the optional conductive agent is typically present in an amount of from 0% to 5% by weight, more preferably from 0% to 2% by weight, of the total amount of solids in the composition, whereas for anode-forming compositions that include a silicon based electroactive compound, it has been found beneficial to incorporate a greater amount of the optional conductive agent, typically from 5% to 20% by weight, of the total amount of solids in the composition.
[0083] The electrode-forming composition (C) of the present invention can be used in a process for producing an electrode, the process comprising the steps of: (A) providing a metal substrate having at least one surface; (B) providing an electrode-forming composition [composition (C)] as defined above; (C) applying the composition (C) provided in step (B) to at least one surface of the metal substrate provided in step (A), thereby providing an assembly comprising a metal substrate coated on at least one surface with said composition (C); (D) drying the assembly provided in step (C); (E) subjecting the dried assembly obtained in step (D) to a compression step to obtain the electrode (E) of the present invention.
[0084] The metal substrate is generally a foil, mesh or net made from a metal such as copper, aluminum, iron, stainless steel, nickel, titanium or silver.
[0085] Under step (C) of the process of the present invention, the electrode-forming composition is typically applied to at least one surface of a metal substrate by any suitable procedure, such as casting, printing, and roll coating.
[0086] Optionally, step (C) can be repeated, typically one or more times, by applying the electrode-forming composition provided in step (B) to the assembly provided in step (D).
[0087] The assembly obtained in step (D) may be further subjected to a compaction step, such as a calendaring process, to achieve the target porosity and density of the electrode.
[0088] Preferably, the assembly obtained in step (D) is hot pressed, the temperature during the pressing step being between 25°C and 130°C, preferably about 90°C.
[0089] A preferred target porosity for the resulting electrode is comprised between 15% and 40%, preferably between 20% and 30%. The porosity of the electrode is calculated as the one's complement of the ratio between the measured density and the theoretical density of the electrode, where: - the measured density is given by the mass divided by the volume of a circular part of the electrode having a diameter equal to 24 mm and a measured thickness, - The theoretical density of an electrode is calculated as the sum of the products of the densities of the electrode's components multiplied by their volumetric ratio in the electrode formulation.
[0090] In a further case, the invention relates to an electrode which can be obtained by the process of the invention.
[0091] Thus, the present invention provides a metal substrate; - (a) at least one vinylidene fluoride (VDF) polymer [polymer (A)], wherein polymer (A) is obtained by a process comprising a step of irradiating polymer (F) with ionizing radiation at a dose of less than 70 kGy, and polymer (F) is (i) a repeating unit derived from vinylidene fluoride (VDF); (ii) at least one vinylidene fluoride (VDF) polymer [polymer (A)], optionally comprising 0.01 mol % to 15.0 mol % of repeat units derived from a fluorinated comonomer (CF) different from VDF, the aforesaid mol percentages referring to the total moles of repeat units of polymer (F); (b) at least one electroactive material (AM); At least one layer adhered directly to at least one surface of said metal substrate, said layer comprising a composition comprising: The present invention relates to an electrode comprising:
[0092] The electrode-forming composition (C) of the present invention is particularly suitable for producing a positive electrode for an electrochemical device.
[0093] The applicant has surprisingly found that the electrode (E) of the present invention exhibits excellent adhesion of the binder to the current collector.
[0094] Therefore, the electrode (E) of the present invention is particularly suitable for use in electrochemical devices, in particular in secondary batteries.
[0095] For the purposes of the present invention, the term "secondary battery" is intended to denote a rechargeable battery. The secondary battery of the present invention is preferably an alkaline secondary battery or an alkaline earth secondary battery. The secondary battery of the present invention is more preferably a lithium ion secondary battery.
[0096] In yet another object, the present invention relates to an electrochemical device comprising at least one electrode (E) of the present invention.
[0097] The electrochemical device according to the present invention is preferably a secondary battery, - Positive and negative electrodes Including, At least one of the positive electrode and the negative electrode is the electrode (E) of the present invention.
[0098] In a preferred embodiment of the present invention, the electrochemical device comprises: - Positive and negative electrodes A secondary battery comprising: It is provided that the negative electrode is an electrode (E) according to the invention.
[0099] Electrochemical devices according to the present invention can be prepared by standard methods known to those skilled in the art.
[0100] To the extent that the disclosures of any patents, patent applications, and publications incorporated herein by reference conflict with the statements of this application to the extent that a term may be unclear, this statement shall control.
[0101] The present invention will now be described with reference to the following examples, the purposes of which are merely illustrative and are not intended to limit the scope of the invention. EXAMPLES
[0102] Experimental section raw materials Polymer (F-1): VDF homopolymer having an intrinsic viscosity of 0.271 l / g in DMF at 25°C and a T2f of 169.8°C.
[0103] Determining the intrinsic viscosity of polymers The intrinsic viscosity (η) [dl / g] was measured using an Ubbelhode viscometer based on the drop time at 25° C. of a solution obtained by dissolving the polymer in N,N-dimethylformamide at a concentration of about 0.2 g / dl, using the following formula:
number
[0104] DSC analysis DSC analysis was performed according to the ASTM D 3418 standard and the melting point (T f2 ) was determined at a heating rate of 10 °C / min.
[0105] Determination of contact angles with water: Preparation of films and measurement of contact angles. Preparation of PVDF films: 1. Prepare a 10 wt% polymer solution in NMP. Dissolve with magnetic stirring at room temperature overnight. 2. The polymer solution is cast onto the glass substrate via doctor blade technique. The blade height is set to reach a final film thickness of about 40um. 3. Dry the membrane overnight at 90° C. with a dry air flow rate of 10 l / min. 4. Remove the film from the glass substrate.
[0106] Water contact angle measurement: The contact angle measurements with water were carried out at room temperature on the shiny side of the film (the side exposed to the glass substrate during the preparation of the membrane) using the following equipment: Contact angle system OCA20 (DataPhysics Instruments GmbH). Solvent: MilliQ water Measurement settings: Droplet Deposition: Automatic Mode Dripping amount=2ml-speed=0.5ml / sec θM = average of 10 drops Laboratory temperature: 23℃
[0107] General preparation of electrodes using NMC active material A positive electrode with a final composition of 96.5 wt % NMC, 1.5 wt % polymer, 2 wt % conductive additive was prepared as follows.
[0108] The first dispersion was prepared by premixing 34.7 g of a 6 wt % solution of polymer in NMP, 133.8 g of NMC, 2.8 g of SC-65, and 8.8 g of NMP in a centrifugal mixer for 10 minutes. The mixture was then mixed for 50 minutes at 2000 rpm using a high-speed disk impeller. An additional 7.2 g of NMP was then added to the dispersion and further mixed for 20 minutes at 1000 rpm using a butterfly impeller. The resulting composition was cast on a 15 μm thick Al foil using a doctor blade, and the coated layer was dried in a vacuum oven at a temperature of 90° C. for about 50 minutes to obtain a positive electrode. The thickness of the dried coating layer was about 110 μm.
[0109] Adhesion peel force method between aluminum and electrode To evaluate the adhesion of the dried coating layer to the Al foil, a 180° peel test was carried out at 20° C. and a speed of 300 mm / min according to the settings described in standard ASTM D903.
[0110] Preparation of Polymer A-1 Polymer (F-1) was treated with 0.6 Mrad of electron beam (beta radiation) radiation. The properties of polymer A-1 are shown in Table 1.
[0111] [Table 1]
[0112] Electrodes were prepared according to the procedure above using polymers F-1 and A-1, and the peel adhesion results are shown in Table 2.
[0113] [Table 2]
[0114] The results surprisingly show that the electrodes prepared using polymer A-1 as a binder have much higher adhesion to metal foils, even at a much lower intrinsic viscosity, than those obtained using polymer F-1, which was not treated with ionizing radiation.
Claims
1. a) at least one electrode active material (AM); b) at least one binder (B), comprising at least one vinylidene fluoride (VDF) polymer [polymer (A)], the polymer (A) being obtained by a process comprising a step of irradiating polymer (F) with ionizing radiation in the presence of oxygen at a dose of less than 70 kGy, the polymer (F) being (i) a repeating unit derived from vinylidene fluoride (VDF); (ii) optionally 0.01 mol % to 15.0 mol % of repeat units derived from a fluorinated comonomer (CF) other than VDF; wherein the mole percentage refers to the total moles of repeat units of the polymer (F); and c) at least one solvent (S); An electrode-forming composition [composition (C)] comprising:
2. The comonomer (CF) different from VDF is (a) C 2 ~C 8 Fluoro- and / or perfluoroolefins, such as tetrafluoroethylene (TFE), hexafluoropropylene (HFP), pentafluoropropylene, and hexafluoroisobutylene; (b) C 2 ~C 8 Hydrogenated monofluoroolefins, such as vinyl fluoride, 1,2-difluoroethylene and trifluoroethylene; (c) Formula CH 2 =CH-R f0 (In the formula, R f0 is C 1 ~C 6 perfluoroalkyl ethylene, (d) Chloro- and / or bromo- and / or iodo-C2 to C6 fluoroolefins, such as chlorotrifluoroethylene (CTFE). The composition (C) according to claim 1, selected from the group consisting of:
3. 2. Composition (C) according to claim 1, wherein the polymer (A) has a contact angle of less than 73°, preferably less than 70°, according to the method reported in the specification.
4. The composition (C) according to claim 1, wherein the irradiation of the polymer (F) is carried out with any ionizing radiation selected from the group consisting of α-rays, β-rays, γ-rays, or electron beams, preferably β-rays, γ-rays and electron beams.
5. Composition (C) according to claim 1, wherein the irradiation of the polymer (F) is preferably carried out with a dosage of from 0.1 kGy to 70 kGy, more preferably from 1 kGy to 40 kGy, even more preferably from 1 kGy to 20 kGy.
6. (A) providing a metal substrate having at least one surface; (B) providing the electrode-forming composition [composition (C)] according to claim 1; (C) applying the composition (C) provided in step (B) to the at least one surface of the metal substrate provided in step (A), thereby providing an assembly comprising a metal substrate coated on at least one surface with the composition (C); (D) drying the assembly provided in step (C); (E) subjecting the dried assembly obtained in step (D) to a compression step to obtain the electrode (E) of the present invention; A process for producing an electrode [electrode (E)] comprising:
7. The process of claim 6, wherein the electrode-forming composition (C) is applied to at least one surface of the metal substrate by any procedure, such as casting, printing, and roll coating.
8. An electrode [Electrode (E)] obtainable by the process according to claim 6.
9. a metal substrate; - (a) at least one polymer (A), which is obtainable by a process comprising a step of irradiating a polymer (F) with ionizing radiation in the presence of oxygen at a dose of less than 70 kGy, and wherein the polymer (F) is (i) a repeating unit derived from vinylidene fluoride (VDF); (ii) optionally, from 0.01 mol % to 15.0 mol % of repeat units derived from a fluorinated comonomer (CF) different from VDF, said mole percentage referring to the total moles of repeat units of polymer (F); (b) at least one electroactive material (AM); at least one layer adhered directly to at least one surface of the metal substrate, the layer comprising a composition comprising: An electrode (E).
10. 10. An electrochemical device comprising at least one electrode (E) according to claim 8 or 9.
11. Preferably, it is a secondary battery, - Positive and negative electrodes Including, The electrochemical device according to claim 10 , wherein at least one of the positive electrode and the negative electrode is an electrode (E).
12. - Positive and negative electrodes A secondary battery comprising: The electrochemical device according to claim 10 , wherein the negative electrode is an electrode (E).